In-patient neurosurgical tumor treatments for malignant glioma patients in Germany - Kamp, Marcel; Fink, Larissa; Forster, Marie-Thérèse; Weiß Lucas, Carolin; Lawson McLean, Aaron; Lawson McLean, Anna; Freyschlag, Christian F.; Stein, Klaus-Peter; Wiewrodt, Dorothee; Mühlensiepen, Felix; Ebner, Florian Heinrich; Rapp, Marion; et al. (Journal of neuro-oncology, 2024)
Objective Treatment for malignant gliomas involves multiple disciplines, including neurosurgery, radiation therapy, medical and neuro-oncology, and palliative medicine, with function-preserving neurosurgical tumor removal being crucial. However, real-world data on hospital cases, treatment types, especially regarding surgical approaches, and the associated complication and mortality rates in Germany are lacking. Methods We analyzed data on hospital cases involving malignant gliomas (ICD-10-GM code C71) from the German §21 Hospital Remuneration Act, provided by the Institute for the Hospital Remuneration System (InEK GmbH), from 2019 to 2022. Our focus was on neuro-oncological operations defined by the German Cancer Society (DKG) and included specific operation and procedure (OPS) codes. Results From 2019 to 2022, there were 101,192 hospital cases involving malignant gliomas in Germany. Neurosurgical tumor removal was performed in 27,193 cases (26.9%). Microsurgical techniques were used in 95% of surgeries, intraoperative navigation systems in 84%, fluorescence-guided surgeries in 45.6%, and intraoperative neurophysiological monitoring (IONM) in 46.4%. Surgical or medical complications occurred in 2903 cases (10.7%). The hospital mortality rate was 2.7%. Mortality was significantly higher in patients aged 65 and older (Odds ratio 2.9, p < 0.0001), and lower in cases using fluorescence-guided procedures (Odds ratio 0.8, p = 0.015) and IONM (Odds ratio 0.5, p < 0.0001). Conclusions Over the course of 4 years, over 100,000 hospital cases involving adult patients diagnosed with malignant gliomas were treated in Germany, with 27,193 cases undergoing tumor removal using various modern surgical techniques. The hospital mortality rate was 2.7%.
Gesehen am 04.06.2025